An Investigation on The Effect of Machine Gauge on the Properties of Weft Knitted Fabric - Reza, Mohammad Hosain; Ahmed, Md. Tanveer (European Scientific Journal, ESJ, 2017)
To investigate the effect of machine gauge on properties of weft knitted fabric, three V – bed knitting machines of different gauges were selected for fabric sample production. They were of gauge 7, 12, and 14. With these three machines, three 1 × 1 rib fabric samples were produced by using 20 / 2 (Ne) yarn. Keeping the same machine settings, 1 × 1 rib fabric samples were produced by using 32 / 2 (Ne) and 40 / 2 (Ne) yarns. The dimensional properties like course / cm, wales / cm, stitch density per square cm, and G.S.M. were measured from the samples. They were tabulated and presented by graphs to observe the effects. To analyze the effects, the stitch length of each fabric’s samples was measured. It was found that the stitch length increases as the machine gauge decreases and vice-versa. As a result, all other properties like; course / cm, wales / cm, stitch density and G.S.M. also changes. It was concluded that the machine gauge affects the knit fabric properties and it has a specific trend.